The hidden burden of adult allergic rhinitis: UK healthcare resource utilisation survey. Issue 1 (December 2015) - Price, David; Scadding, Glenis; Ryan, Dermot; Bachert, Claus; Canonica, G.; Mullol, Joaquim; Klimek, Ludger; Pitman, Richard; Acaster, Sarah; Murray, Ruth; Bousquet, Jean
Abstract Background The affliction of allergic rhinitis (AR) has been trivialised in the past. Recent initiatives by the European Academy of Allergy & Clinical Immunology and by the EU parliament seek to rectify that situation. The aim of this study was to provide a comprehensive picture of the burden and unmet need of AR patients. Methods This was a cross-sectional, online, questionnaire-based study (June–July 2011) including symptomatic seasonal AR (SAR) patients (≥18 years) from a panel. SAR episode pattern, severity, medication/co-medication usage, residual symptoms on treatment, number of healthcare visits, absenteeism and presenteeism were collected. Results One thousand patients were recruited (mild: n = 254; moderate/severe: n = 746). Patients with moderate/severe disease had significantly more symptomatic episodes/year (8.0 vs 6.0/year; p = 0.025) with longer episode-duration (12.5 vs 9.8 days; p = 0.0041) and more commonly used ≥2 AR therapies (70.5 vs 56.1 %; OR 1.87; p = 0.0001), looking for better and faster nasal and ocular symptom relief. The reported symptom burden was high irrespective of treatment, and significantly (p < 0.0001) higher in the moderate/severe group. Patients with moderate/severe AR were more likely to visit their GP (1.61 vs 1.19 times/year; OR: 1.49; p = 0.0061); due to dissatisfaction with therapy in 35.4 % of cases. Patients reported SAR-related absenteeism from work on 4.1 days/year (total cost to UK: £1.25 billion/year) and noted presenteeism for a mean of 37.7 days/year (vs 21.0 days/year; OR 1.71; p = 0.0048). Asthma co-morbid patients reported the need to increase their reliever- (1 in 2 patients) and controller-medication (1 in 5 patients) if they did not take their rhinitis medication. Conclusions This study differentiated between patients with mild and moderate/severe AR, demonstrating a burden of poorly controlled symptoms and high co-medication use. The deficiency in obtaining symptom control with what are currently considered firstline treatments suggests the need for a novel therapeutic approach.